MANAJEMEN PEMBELAJARAN BAHASA INGGRIS MENGGUNAKAN METODE CONTROL TO FREE UNTUK MENINGKATKAN KEMAMPUAN MENULIS TEKS REPORT BAGI SISWA SMP - Byuti Byuti (UNIVERSITAS BENGKULU, 2017)
In SMP 1 Ujan Mas Kepahiang, there are many nine grade students find difficulties in writing observative text. Because of that, the researcher tries to use control to free method to solve the problems. The result of the observation shows that the students look anxious to attend the lesson when control to free method is used in learning writing. The result of first ciclus, there are 4 students couldn’t reach the minimum criterion mark. And in the second cyclus, there are 2 students couldn’t reach the minimum criterion mark